The Sexual Behaviour of Chagas' Disease Vectors: Chemical Signals Mediating Communication between Male and Female Triatomine Bugs - Gabriel Manrique; Marcelo Lorenzo (Psyche: A Journal of Entomology)
Chemical communication mechanisms that mediate sexual behaviour in triatomine bugs are reviewed with regard to source, identity, and function of sex pheromones. Males attempt to copulate but may be rejected, depending on female age and nutritional status. Triatomine males locate partners through sex pheromones emitted by the metasternal glands (MGs) of females. These activate males, inducing them to leave their refuges and initiate flight. Wandering males display anemotactic orientation modulated by chemical signals emitted from female MGs. Analyses of the MG secretions of several species resulted in the identification of numerous ketones, acetals, and alcohols. Occlusion experiments showed that Brindley’s gland products were not required for mating. Metasternal gland volatiles are emitted by virgin male and female bugs, with detection over females occurring more consistently, especially during the early scotophase, suggesting female calling behaviour. Mating triatomine females have been reported to attract males that tend to copulate successively with them. Mating males prolong mating and postcopulatory mate guarding in the presence of other males. This is indicative of a polyandrous mating system in several triatomine species. Its potential advantages remain unknown, and comparative studies are required to increase our understanding of triatomine reproductive strategies.